An integrated payroll-pension system - Hwang, Evelyn L (Department of Computer Science, 2015)
An integrated payroll-pension system designed specifically for commercial users with limited computer resources is presented. This system combines in a single system the usual functions of both a payroll system and a pension system. Apart from economies which result from reduced software requirements and minimized duplication of files, the particular integration approach adopted leads to the inclusion, within the system design, of numerous capabilities normally associated only with a computerized personnel system. The integrated system has been so designed that it can serve eventually as a nucleus for a personnel information system.